Comments on Directive (EU) 2019/1937 of the European Parliament and of the Council of 23 October 2019 on the Protection of Persons Who Report Breaches of Union Law - dos Santos, Jorgete Vitorino Clarindo; Nemer, Tania (University of Wroclaw. Faculty of Law, Administration & Economics, 2021)
Without some of the important information brought into light by whistleblowers, many current scandals would not have occurred. It is undeniable that whistleblowing brought into the public domain can insert a previously unforeseen and incorrigible milestone in the biography of whistleblowers, which can lead to financial loss, loss of work, affect private life, and even health. Even in situations where the whistleblower acts in good faith, he runs the risk of being publicly judged and having his reputation tarnished by lack of protection. Reporting persons may even be driven to complete isolation or pay with their lives or that of their families. In view of this, the European Union has foreseen in a new directive a better protection for whistleblowers, through the implementation of a trilateral whistleblower system. The main new feature of the European Whistleblower Protection Directive is the obligation to establish internal whistleblower channels for legal entities in the public and private sectors with at least 50 or more employees. In the public sector, Member States may exempt cities with fewer than 10,000 inhabitants or fewer than 50 employees working in the public body from the obligation to establish whistleblowing channels. If the report to the company or public body is not successful, the whistleblower may report to the press. European legislators have until December 2021 to transpose the provisions of this directive into national whistleblower protection regulations.
Keywords: compliance; whistleblowing channel; protection; whistleblower; directive European Union; U.S. DOJ